PERBANDINGAN KADAR SINEOL DARI MINYAK KAYU PUTIH PRODUKSI TRADISIONAL DAN MODERN - usman, Sri mayang usman mayang (UNIVERSITAS MUSLIM INDONESIA, 2024)
ABSTRACT Eucalyptus oil is an oil that has been commonly used in the lives of Indonesian people. Eucalyptus oil is an essential oil obtained by distilling the leaves and twigs of the eucalyptus plant. Eucalyptol (1,8-Sineol) is a monoterpene compound that has anti-inflammatory and antioxidant properties. Usually used to treat airway disorders. This study aims to identify the comparison of sineol content of eucalyptus oil from traditional and modern production. This research method was carried out using densitometry and GC MS. The results obtained in densitometry clusters are the highest levels of sineol in the eucalyptus leaf comparator, namely 451.2%, while in eucalyptus oil there is traditional eucalyptus oil (ambon), namely 198.7%, whose sineol content is higher than the modern eucalyptus oil sineol content, which is 67.13%. For the results obtained on GC-MS, the highest level of sineol in traditional eucalyptus oil (ambon) is 52.65% compared to modern eucalyptus oil which is 32.11% and also the comparison of eucalyptus leaves which is 0.28%. Keywords : Eucalyptus oil; traditional; modern; sineol ; KLT Densitometro; GC-MS.